BIMBINGAN PENYUSUNAN DOKUMEN I KURIKULUM BERBASIS FORMASI SIBERPRO: UPAYA MENGATASI KETERSEDIAAN DOKUMEN KURIKULUM PADA MADRASAH BINAAN - Nurtiah Kadir (Jurnal Teknologi Pendidikan Madrasah, 2018)
The position of supervisor is very strategic and will affect the quality of education as a whole. Supervisors are functional and responsible for the occurrence of learning, education, and guidance processes within the education unit at various levels and types of education. Its strategic function will be able to improve the process of learning and guidance carried out by the teacher so that the education process will take place effectively, especially in the educational environment. This research is an action research Guidance for Preparing Curriculum Documents Based on a Verification Format: Systematic, Correct, and Procedural (FORMASI SIBERPRO). The number of Madrasas assisted has 100% curriculum documents. The number of trained madrasas has curriculum documents with qualifications: very good 80%. Whereas 20% of Madrasas assisted have good qualified curriculum documents. Implementation of guidance on the preparation of document 1 curriculum with the Siberpro Pharmacy approach is very effective in overcoming the weaknesses of madrasas in the preparation of curriculum documents. Based on 3 (three) required criteria: systematic, correct, and procedural, the results of document 1 development guidance show that achievement is very good on average. Guidance for the preparation of documents 1 of the Siberpro Formation-based curriculum can be developed and disseminated in a wider scope, both provincial and national scale.